Pengaruh Paku Sebagai Bahan Tambah Terhadap Kuat Tarik Belah Beton - Sarya, Gede; Rochmah, Nurul; Lukmansyah, Indra (JHP17 (Jurnal Hasil Penelitian), 2018)
The use of concrete for construction materials is currently in demand because theconcrete has advantages such as high compressive strength, easy maintenance after theconcrete is crushed and easily formed to suit the needs. Among the advantages of theconcrete also has a defect that is brittle and has a tensile strength of about ten percent of thecompressive strength. Disadvantages of the concrete can be overcome by adding fiber to theconcrete mixture, can be called fiber concrete (fiber concrate). In this study the use of specialstainless steel factory-made as an additional material will be replaced with other materialsthat is nails. The results to be tested include compressive strength and tensile strength of thevariation of spikes 0%, 2% and 4% were tested for 7 days and 28 days of test subjects of 36units. The results obtained from this research process is a decrease in compressive strength asthe variation of spikes increases and vice versa increases the tensile strength as the spikesincrease.Keywords: Normal Concrete. Fiber Concrete. Fiber Steel